ROLE AND CHALLENGES OF HOSPITAL PHARMACISTS WORKING IN LIAQUAT UNIVERSITY HOSPITAL HYDERABAD/ JAMSHORO, A PUBLIC SECTOR HOSPITAL, PAKISTAN - Sahib Khan Meer ani; Chaudhry Muhammad Amjad; Muhammad Ibrahim Ansari et al. (Journal of University Medical & Dental College, 2018)
ABSTRACT: INTRODUCTION: Hospital Pharmacist plays vital role and challenge in public sector. It is important component of health care system. AIM OF THE STUDY: To institutionalize Hospital Pharmacists in the Public Sector Health System. OBJECTIVES: To assess role of Hospital Pharmacists currently working, to identify Hospital Pharmacists’ experience and the factors inﬂuencing while working in Public Sector in Liaquat University Hospital, Hyderabad/ Jamshoro. METHOD AND DESIGN: Descriptive Cross-sectional study was carried out in District Hyderabad/ Jamshoro with census sampling of Hospital Pharmacists. Duration of study was from Oct 2016 to Feb 2017. Self-administered questionnaire was developed from the job description of Hospital Pharmacists provided by the Health Department, GoS for study to assess role of Hospital Pharmacists. Questionnaire has 4 parts include the questions on the duties, responsibilities, recognition, development and working environment for Hospital Pharmacists. The data was analyzed in SPSS IBM version 21.0. RESULTS: 26 Hospital Pharmacists participated, among them 04(16%) were female and 22 (84%) were male. Majority of the participants (55%) were in the age group 25-35 years. Response rate was 96%. The mean age was calculated as +34 years with monthly income of +40000 PKR and mean of job experience was +7 Years. Majority were having basic education of Pharm D. CONCLUSIONS: Study results showed that there is a dire need of institutionalizing and proper training of the Hospital Pharmacist(s) in Liaquat University Hospital, Hyderabad/ Jamshoro.